EFFECT OF LASER ACUPUNCTURE THERAPY ON THE PAIN IN HANSEN'S DISEASE PATIENTS IN COMPARISON WITH ACUPUNCTURE - OHTAKA, Koh; TAKAHASHI, Yasuko (Japanese Journal of National Medical Services, 1991)
Effect of laser acupuncture on pain was clinically studied in patients with Hansen's disease. The subjects were 63 cases suffering from pain in various areas of the body; head, face, neck, back, limbs, foot and hand, including muscular contracture headache and ischias. Stimulating points were selected in the painful area according to the “Ryodoraku” theory, and stimulated by Ga-AI-As semiconductor laser (λ 790nm, 10mw) for 20-40 sec, 6 times a week within 40 days with use of MIO-60 Uni-laser (MERECO, Osaka). Pain-relief was obtained in 93.4 percent of the cases. In most cases, pain was relieved by 5 to 10 times-irradiation of the laser. No side-effect was seen. The analgetic effect continued for one to 14 months in the cases of facial pain or headaches, for 5 days to 6 months in the cases of shoulder pain. As compared with author's previous result, laser acupuncture is more effective to relieve pain in Hansen's disease.